2001
DOI: 10.1007/pl00011200
|View full text |Cite
|
Sign up to set email alerts
|

Remission of the Renal Involvement in a Patient with Primary Sjo¨gren’s Syndrome (SS) after Pulse High-Dose Corticosteroid Infusion Therapy

Abstract: We report the case of a young female patient with primary Sjögren's syndrome (SS). In addition to sicca symptoms she also suffered from progressive renal insufficiency and renal tubular acidosis (RTA). She was treated with three sets of pulse high-dose corticosteroid infusion and subsequent low-dose corticosteroid oral administration. When the efficacy was evaluated about 6 months after the start of the therapy, dramatic improvements were seen with no adverse effects, not only in laboratory tests but also hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…Eighteen studies reported the management of 32 patients with pSS and biopsyproven renal disease: 14 with IN, 16 GN, and two IN+GN (9,16,18,19,21,24,26,35,36,40,47,48,50,52,(54)(55)(56)(57). Seventeen patients were treated with a combination of corticosteroids and cyclophosphamide, and 15 patients received only steroids with improvement in the majority of cases (Table 1).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Eighteen studies reported the management of 32 patients with pSS and biopsyproven renal disease: 14 with IN, 16 GN, and two IN+GN (9,16,18,19,21,24,26,35,36,40,47,48,50,52,(54)(55)(56)(57). Seventeen patients were treated with a combination of corticosteroids and cyclophosphamide, and 15 patients received only steroids with improvement in the majority of cases (Table 1).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They concluded that TIN associated with SS has proved to be a rather benign condition, as none of the patients presented with end-stage renal failure. On the other hand, cases of TIN with renal failure have been reported; [8][9][10][11] and although there have been no controlled studies on renal failure, corticosteroids and cytotoxic drugs are empirically used with frequently favorable outcomes. Moreover, no patients with TIN who presented with renal failure requiring continuous hemodialysis have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Combination of corticosteroids and other immunosuppressants have been reported to slow progression of renal damage in Sjogren's syndrome2 8 but the efficacy of the treatment has been largely demonstrated only in patients with rapidly progressing renal damage or insufficiency 2 8 9. In fact, in a case reported by Reddy et al 10, hypokalaemia and acidosis recurred after tapering the dose of prednisolone, having given it for 6 months.…”
Section: Discussionmentioning
confidence: 99%